Case 3768: Hybosorus illigeri Reiche, 1853 (Insecta, Coleoptera): proposed conservation by giving it precedence over Hybosorus pinguis Westwood, 1845, Hybosorus roei Westwood, 1845 and Hybosorus carolinus LeConte, 1847 - Ballerio, Alberto; Krell, Frank-Thorsten; Bezděk, Aleš; Frolov, Andrey; Huchet, Jean-Bernard; Keith, Denis; López-Colón, José Ignacio; Matthews, Eric; Ocampo, Federico; Rey, Antonio; Vaz-de-Mello, Fernando Z (Bulletin of Zoological Nomenclature, 2018)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the widely used specific name Hybosorus illigeri Reiche, 1853 (Coleoptera: Scarabaeoidea, Hybosoridae), a globally widespread and common scarab beetle. The name is threatened by the very rarely used senior subjective synonyms Hybosorus pinguis Westwood, 1845, Hybosorus roei Westwood, 1845, and Hybosorus carolinus LeConte, 1847. Precedence of the name Hybosorus illigeri is proposed to maintain stability of nomenclature.
Keywords: Nomenclature; taxonomy; Coleoptera; HYBOSORIDAE; Hybosorus illigeri; Hybosorus roei; Hybosorus carolinus